Antiseizure medication discovery: Recent and future paradigm shifts. (7th February 2022) - Talevi, Alan
Abstract: Despite the ever‐increasing number of available options for the treatment of epilepsies and the remarkable advances on the understanding of their pathophysiology, the proportion of refractory patients has remained approximately unmodified during the last 100 years. How efficient are we translating positive outcomes from basic research to clinical trials and/or the clinical scenario? It is possible that fresh thinking and exploration of new paradigms are required to arrive at truly novel therapeutic solutions, as seemingly proven by recently approved first‐in‐class antiseizure medications and drug candidates undergoing late clinical trials. Here, the author discusses some approximations in line with the network pharmacology philosophy, which may result in highly innovative (and, hopefully, safer and/or more efficacious) medications for the control of seizures, as embodied with some recent examples in the field, namely tailored multi‐target agents and low‐affinity ligands.